Daily smoking and lower back pain in adult Canadians: the Canadian Community Health Survey - Fahad Alkherayf; Eugene K Wai; Eve C Tsai; et al (Journal of Pain Research, 2010)
Fahad Alkherayf1,2,3, Eugene K Wai4,5,6, Eve C Tsai1,3,4,6, Charles Agbi1,3,41University of Ottawa, Division of Neurosurgery, Ottawa, Ontario; 2University of Ottawa, Department of Clinical Epidemiology, Ottawa, Ontario; 3The Ottawa Hospital, Civic campus, Division of Neurosurgery, Ottawa, Ontario; 4The Ottawa Hospital, Civic Campus, Spine Unit Ottawa, Ontario; 5The Ottawa Hospital, Civic Campus, Division of Orthopedic Surgery, Ottawa, Ontario; 6The Ottawa Hospital Research Institute, Ottawa, Ontario, CanadaBackground: Lower back pain (LBP) is one of the primary causes of disability in the Canadian community. However, only a limited number of studies have addressed the association between daily smoking and LBP in Canada. Of the studies that have explored this association, many had small sample sizes and failed to control for confounders.Objective: The primary objective of the study was to determine if daily smoking is associated with an increased risk of having LBP. The secondary objectives were to assess the risk for LBP among occasional smokers and to determine the prevalence of LBP in relation to different covariates.Data and study design: Using the Canadian Community Health Survey (cycle 3.1) data, 73,507 Canadians between the ages of 20 and 59 years were identified. LBP status, smoking level, sex, age, body mass index (BMI), level of activity and level of education were assessed in these subjects.Methods: Stratified analysis and logistic regression analysis were used to detect effect modifications and to adjust for covariates. Population weight and design were taken into consideration.Results: The prevalence of LBP was 23.3% among daily smokers and 15.7% among non-smokers. Age and sex were found to be effect modifiers. The association between LBP and daily smoking was statistically significant in all ages and genders; this association was stronger for younger age groups. The adjusted odds ratio for male daily smokers aged 20 to 29 was 1.87 (95% CI = 1.62, 2.17); findings were similar for women. Occasional smoking slightly increased the odds of having back pain.Conclusion: Young Canadian daily smokers are at higher risk for LBP. This study also suggests a positive correlation between smoking dose and the risk of LBP. These findings indicate that smoking behavioral modification may have an impact on reducing back pain especially among young adults.Keywords: lower back pain, smoking, Canadian Community Health Survey, sex, adult Canadians